Dėl įvardžiuotinių būdvardžių kirčiavimo raidos - Mikulėnienė, Danguolė (Baltistica, 1994)
CONCERNING THE DEVELOPMENT OF THE ACCENTUATION OF PRONOMINAL ADJECTIVESThe pronominal adjective accentuation is hypothesised this way: according to de Saussure’s law, the ictus was retracted both from the acute and circumflex syllables to the following acute syllable.